Global Cooperative Economics and Movements (Taylor & Francis, 2026)
Cooperatives are traditionally recognized as marginal players in the economic sector, but their role in policymaking and in social arenas has garnered even less attention. Over the past two decades, an extensive body of literature in management science and economics has arisen, designating non-capitalistic enterprises as subjects of particular attention. In the context of rising global challenges like economic inequality, environmental sustainability, and labor rights, the role of cooperatives has become increasingly relevant. This book examines the practical and policy dimensions and implications of cooperative economics and movement(s). It delves into the more politicized aspects of cooperatives, exploring how they intersect with global movements, social justice, policymaking, and grassroots activism and provides insights into real struggles tackled by this enterprise form. It offers an understanding of how communication in cooperatives plays a role in promoting principles, values and practices and how these are transferred across generations of cooperators. It provides a deeper understanding of the elements of intergenerational evolution within cooperatives in concepts on employment and labour as new policies are raising expectations. Further, it offers a broad variety of global case studies pertinent to issues of relevance to cooperative economics and management, profiling how different types of cooperatives on six continents can promote sustainability and self-organized community wealth-generation, connecting to development studies, ethics and political economy, while revealing how cooperatives can address the current challenges of the digital age, especially including issues of data governance and artificial intelligence. The book will serve as an invaluable tool for anyone seeking to understand the broader implications of cooperative models in today's globalized world. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-ShareAlike (CC-BY-SA) 4.0 license.